The Effect of Palm Oil Ash Ash on Micro Nutrient Uptake by Soybean Roots in Peatlands - Intan Sari (Baselang, 2021)
Research on the potential of oil palm cassava ash as an ameliorant in increasing micronutrient uptake by soybean roots on peat soil was carried out from August 2020 to February 2021, at the wire house of the Faculty of Agriculture, Indragiri Tembilahan Islamic University, Riau Province. The purpose of this study was to observe the interaction between the dose of Palm Oil Ash (AJKS) and nutrient uptake by the roots of several soybean varieties and to obtain the optimum dose of AJKS in increasing the uptake of micro nutrients Cu, Zn, Fe and Mn by soybean roots. the Tanggamus, Slamet and Anjasmoro varieties.            This study used a separate plot design with 3 treatments as main plots were 3 soybean varieties: V1 = Tanggamus variety (tolerant), V2 = variety, Slamet (moderate), V3 = Anjasmoro variety (sensitive). The sub-plots were 4 doses of AJKS administration consisting of: A0 = Without AJKS treatment, A1 = 300 kg/ha AJKS, A2 = 600 kg/ha AJKS and A3 = 900 kg/ha AJKS with 3 replications. The results of the study concluded that the application of oil palm cassava ash (AJKS) in general increased the uptake of micronutrients by soybean plant roots on peatlands. There was an interaction between the dose of AJKS and soybean varieties on the absorption of Cu, Zn and Fe in the roots of Tanggamus, Slamet and Anjasmoro soybeans. Administration of 900 kg/ha AJKS gave the highest micronutrient uptake of Cu, Zn, Fe and Mn both in Tanggamus, Slamet and Anjasmoro varieties, but optimal results were generally achieved at a dose of 600 kg/ha AJKS.